Prehospital Management of Pediatric Hanging. Issue 4 (April 2018) - Rehn, Marius; Davies, Gareth; Foster, Elizabeth; Lockey, David J.
Abstract : Objectives: Hanging may inflict laryngotracheal injuries and increase the potential for difficult airway management. We describe the management of pediatric hangings attended by an urban physician-led prehospital trauma service to provide information on a clinical situation encountered infrequently by most acute care clinicians. Methods: Retrospective trauma registry-based observational study of all children younger than 16 years attended with hanging as mechanism of injury in the period between 2000 and 2014. Results: Twenty-three thousand one hundred thirty patients were attended; 2415 (10%) of which were children. Of these, 32 cases (<1%) were pediatric hanging (1 case excluded due to missing data). There were 22 (71%) boys and 9 (29%) girls. Median age was 13 years. There was suicidal intent in 23 (74%) cases, and in 8 (26%) cases, hanging was accidental. There were 17 (55%) deaths, of which 14 (82%) were suicides. The doctor-paramedic team intubated 25 (80%) patients, with a 100% success rate. One (3%) patient was managed with a supraglottic airway device, and 5 (16%) patients did not require any advanced airway management. Conclusions: Pediatric hanging is rare, but has a high mortality rate. Attempted suicide is the leading cause of hangings in children and preventive measures should target psychiatric morbidity. Despite concerns about airway edema or laryngeal injury, experienced doctor-paramedic teams had no failed airway attempts.